RENCANA PROGRAM SUPERVISI DAN EVALUASI PENDIDIKAN: SUPERVISI TERHADAP PERENCANAAN PEMBELAJARAN, SUPERVISI TERHADAP LANGKAH PEMBELAJARAN DAN SUPERVISI TINDAK LANJUT - Andina Nur Fadlila; Purwo Septri Nugroho; DwiRahman Afandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article aims to design a comprehensive supervision program plan covering three main domains: supervision of learning planning, supervision of learning steps, and follow-up supervision. The background of this research is the importance of improving the quality of learning through a systematic and sustainable academic supervision approach, not just an inspection of teacher performance. The research method used is library research, with data analysis techniques through in-depth study of literature on supervision concepts, clinical approaches, and the preparation of operational instruments and programs. The results of the study indicate that an effective supervision program is implemented through three integrated stages. First, planning supervision uses document checklists to ensure the quality of the Lesson Plan (RPP). Second, the supervision of learning steps is carried out through a clinical supervision cycle (preobservation, observation, and post-observation) to observe the implementation of learning in the classroom. Third, follow-up supervision is carried out through analysis of results, mentoring, ongoing training, and monitoring evaluation. The conclusion of this article is that successful supervision is measured by the increase in teacher competency and the quality of learning, which is realized through a cycle of planning, implementation, and sustainable follow-up